Activin and BMP Signaling Activity Affects Different Aspects of Host Anti-Nematode Immunity in Drosophila melanogaster - Ozakman, Yaprak; Raval, Dhaivat; Eleftherianos, Ioannis (Frontiers in Immunology, 2021)
The multifaceted functions ranging from cellular and developmental mechanisms to inflammation and immunity have rendered TGF-ß signaling pathways as critical regulators of conserved biological processes. Recent studies have indicated that this evolutionary conserved signaling pathway among metazoans contributes to the Drosophila melanogaster anti-nematode immune response. However, functional characterization of the interaction between TGF-ß signaling activity and the mechanisms activated by the D. melanogaster immune response against parasitic nematode infection remains unexplored. Also, it is essential to evaluate the precise effect of entomopathogenic nematode parasites on the host immune system by separating them from their mutualistic bacteria. Here, we investigated the participation of the TGF-ß signaling branches, activin and bone morphogenetic protein (BMP), to host immune function against axenic or symbiotic Heterorhabditis bacteriophora nematodes (parasites lacking or containing their mutualistic bacteria, respectively). Using D. melanogaster larvae carrying mutations in the genes coding for the TGF-ß extracellular ligands Daw and Dpp, we analyzed the changes in survival ability, cellular immune response, and phenoloxidase (PO) activity during nematode infection. We show that infection with axenic H. bacteriophora decreases the mortality rate of dpp mutants, but not daw mutants. Following axenic or symbiotic H. bacteriophora infection, both daw and dpp mutants contain only plasmatocytes. We further detect higher levels of Dual oxidase gene expression in dpp mutants upon infection with axenic nematodes and Diptericin and Cecropin gene expression in daw mutants upon infection with symbiotic nematodes compared to controls. Finally, following symbiotic H. bacteriophora infection, daw mutants have higher PO activity relative to controls. Together, our findings reveal that while D. melanogaster Dpp/BMP signaling activity modulates the DUOX/ROS response to axenic H. bacteriophora infection, Daw/activin signaling activity modulates the antimicrobial peptide and melanization responses to axenic H. bacteriophora infection. Results from this study expand our current understanding of the molecular and mechanistic interplay between nematode parasites and the host immune system, and the involvement of TGF-ß signaling branches in this process. Such findings will provide valuable insight on the evolution of the immune role of TGF-ß signaling, which could lead to the development of novel strategies for the effective management of human parasitic nematodes.